12 STUDY ON FACTORS AFFECTING THE PERFORMANCE OF CONSTRUCTION PROJECTS IN THE DEMOCRATIC REPUBLIC OF THE CONGO - Bitamba, B F; An, S H (The South African Journal of Industrial Engineering, 2020)
The Congolese construction industry faces many difficulties in dealing with the different factors that affect the proper performance of the construction process. Several key indicators (factors) that influence the construction performance in the Congo were selected for study and discussion. This study aimed to identify and evaluate the most significant key performance indicators that affect construction projects in the Congo, and to classify them using the relative importance index (RII). The most important factors affecting Congolese construction projects were design, client management, contractor productivity, scheduling, and the contract. The experience and skill of the design team were found to affect the design-related factors, whereas delayed payments and delivery of the construction site to the contractor were found to be the most important factors affecting client/owner-related factors. Client and management factors shared an equal average significant value of 0.68, while the productivity scheduling and contract related factors for the contractor shared an equal average value of 0.67. Finally, this work makes some recommendations to the Congolese construction industry in order to ensure proper project performance and successful projects.